SHM_1227378_HST_3D Pointed-Butted Stone Axe - National Historical Museums (National Historical Museums, 2026)
A structured light 3D model of a pointed-butted stone axe from the Swedish Neolithic, collected from Lofta Parish in Småland and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=399

Link to Sök I Samlingarna

https://samlingar.shm.se/object/4A929157-DDA9-46EB-A0E4-13ADB6CF9B54
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Dynamic Collections; Lofta; 3D Model; Structured Light Scanning; Museum Object; Swedish Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi